The Use Of Slang Language Style On Social Media Instagram By Gen-Z (Generation Z) - Syaputra, Ary Rahmad; Sari, Sapta; Endang, Anis (Universitas Dehasen Bengkulu, 2024)
Along with the times, advances in communication and information technology also have an impact on the cultural aspects of society, especially on the use of social media by Generation Z - a generation born in the era of information technology. The development of social media has led to the emergence of a new language style, which is often referred to as